2021
DOI: 10.7717/peerj.11349
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 rs7903146 polymorphism association with diabetes and obesity in an elderly cohort from Brazil

Abstract: Background Type 2 diabetes mellitus (T2DM) and obesity are complex pandemic diseases in the 21st century. Worldwide, the T allele rs7903146 in the TCF7L2 gene is recognized as a strong GWAS signal associated with T2DM. However, the association between the C allele and obesity is still poorly explored and needs to be replicated in other populations. Thus, the primary objectives of this study were to evaluate the TCF7L2 rs7903146 association with T2DM according to BMI status and to determine if this variant is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
5
0
4
Order By: Relevance
“…It contains a DNA- binding domain, is implicated in the regulation of cell proliferation and differentiation, and maintains the stability of plasma glucose [ 28 , 29 ]. TCF7L2 is related with T2DM risk and DM complications such as diabetic nephropathy, and is also a susceptibility locus for CRC [ 12 , 15 , 30 ]. In the present study, the genotype distribution of the TCF7L2 rs7903146 polymorphism was correlated with susceptibility for CRC and DM in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains a DNA- binding domain, is implicated in the regulation of cell proliferation and differentiation, and maintains the stability of plasma glucose [ 28 , 29 ]. TCF7L2 is related with T2DM risk and DM complications such as diabetic nephropathy, and is also a susceptibility locus for CRC [ 12 , 15 , 30 ]. In the present study, the genotype distribution of the TCF7L2 rs7903146 polymorphism was correlated with susceptibility for CRC and DM in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor 7-like 2 ( TCF7L2 ) gene, 10q25.2–q25.3, is a transcription factor and β-catenin transcription partner in the Wnt signaling pathway that represses gene transcription in the absence of β-catenin after DNA-binding and also promotes miR-21 expression [ 9 , 10 , 11 ]. There are studies that have confirmed an association between TCF7L2 rs7903146 and T2DM [ 12 , 13 , 14 , 15 ], and a weak association with CRC [ 16 , 17 , 18 ]. Another polymorphism, rs6983267, is located in Cancer Susceptibility Candidate 8 Noncoding (CASC8) 8q24.21 and the risk allele promote stronger TCF7L2 binding, facilitating Wnt signaling [ 9 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TCF7L2 variants were also linked to a faster decline in pancreatic ß-cell function, higher glycemic levels, and lower insulin production, all of which are linked to familial history of T2D 66 . Other studies have shown that the TCF7L2 rs 7903146T genotype is associated with both T2D and obesity, and that carriers may have changes in their plasma metabolic profiles due to phospholipids, suggesting that phospholipids may cause metabolic abnormalities prior to the onset of glucose intolerance 67 , 68 . These effects were recently brought to light by research demonstrating that the TCF7L2 gene controls a number of processes, including adipogenesis and disorders like T2D, as a downstream effector of the Wnt/ß-catenin signaling system 69 .…”
Section: Pharmacological Aspects Of Metforminmentioning
confidence: 99%
“…The search string results had an output of 29,092 articles and from these, 101 articles were identified as potential studies. After the full-text screening, 27 articles were excluded for the following reasons: six studies were not based on LACP (35)(36)(37)(38)(39)(40), five studies aimed to identify the effect of genomic ancestry (41)(42)(43)(44)(45), six studies focused only on genetic associations (46)(47)(48)(49)(50)(51), eight studies did not include cardiometabolic diseases (52)(53)(54)(55)(56)(57)(58)(59), and two studies investigated gene x phenotype interactions (60,61) as shown in Figure 5. Finally, after excluding the irrelevant articles based on the exclusion criteria, 74 studies were included in this systematic review as shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%